Pengaruh Corporate Governance Dan Arus Kas Operasi Terhadap Financial Distress - Karina Dilla Ovtaviani; Eka Rima Prasetya (Akuntansi, 2024)
This study aims to determine the effect of corporate governance represented by institutional ownership and managerial ownership as well as operating cash flow on financial distress conditions in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. Financial distress conditions are measured using the Zmijewski model. The analysis method used is panel data regression with the help of Eviews 9 software. Through a purposive sampling approach, 24 companies were selected that fit the research criteria. The results showed that partially, institutional ownership and managerial ownership have no influence on financial distress, while operating cash flow has an influence on financial distress. Jointly, the three variables namely institutional ownership, managerial ownership, and operating cash flow are proven to have an influence on financial distress.